A globally asymptotically stabilizing trajectory tracking controller for fully actuated rigid bodies using landmark‐based information. (29th December 2014) - Casau, Pedro; Sanfelice, Ricardo G.; Cunha, Rita; Silvestre, Carlos
Summary: In this paper, we address the problem of designing a control law based on sensor measurements that provides global asymptotic stabilization to a reference trajectory defined on the SE ( 3 ) × R 6 . The proposed control law is a function of the angular velocity, of vector measurements characterizing the position of some given landmarks, and of their rate of change. We provide sufficient conditions for the existence of synergistic potential functions on S O (3) which are pivotal in the generation of a suitable hybrid control law. We also provide sufficient conditions on the geometry of the landmarks to solve the given problem. Finally, the proposed solution is simulated and compared with a continuous feedback control law. Copyright © 2014 John Wiley & Sons, Ltd.